Fertility trends and levels in Lattakia city (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Fertility levels in any society are the product of the interaction of demographic, economic, cultural and sometimesevenpoliticalfactorswitheachother in the geographicalspace. The phenomenon of fertilityis a complexprocessassociatedwith the continuity and survival of humanity. Countries vary in the direction of reproductive behaviour.In thisresearch, wewilltry to shed light on fertilitylevels and extrapolatetheir future trends in the city of Lattakia, whichconstitute the most important demographicfactorsthatplaya key role in determining population growth rates according to someindicatorssuch as the crudebirth rate and the syntheticfertility index. Especiallysince Lattakia isconsidered one of the lowestfertility rates compared to the rest of the governorates.